REAKTUALISASI NILAI-NILAI KEISLAMAN MELALUI IMPLEMENTASI PROJEK PENGUATAN POFIL PELAJAR PANCASILA DAN PROFIL PELAJAR RAHMATAN LILALAMIN (P5-PPRA) - D. Abdul Kohar; Asep Abdullah; Adang Hambali; Hasan Basri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research uses a qualitative approach with a case study method focusing on identifying facilitators strategies in reactualizing Islamic values ​​in P5-PPRA activities carried out at MTsN 6 Cianjur, identifying reactualizd Islamic values ​​in the project, and finding out students’ perceptions of the project activities. Data collection instruments use interviews and observation, and data analysis uses the steps namely reducing, displaying and drawing conclusions. The research results show that MTsN 6 Cianjur facilitators carry out project activities to strengthen the Pancasila student profile and the Rahmatan Lilalamin student profile (P5-PPRA) with a co-curricular strategy, namely project activities that are designed separately from intracurricular or regular learning activities. The actualized Islamic values ​​are faith in Allah and His Messenger, patience, responsibility, gratitude, tawadu, not being arrogant and haughty, tolerance and criticism, mutual cooperation, helping each other and equality (musawwa), innovation and love of the country. The students like the activities of the project to strengthen the Pancasila student profile and the Ralmatan Lilalamin student profile (P5-PPRA) although there are still students who pay little attention to these activities due to various factors such as family, health, economic and friend problems. Keywords: P5-PPRA, Islamic values, Madrasah.